Case report: Uncommon immune-mediated skin disease involving systemic disorders in dogs - Kim, Soomin; Kim, Yoonji; Kim, Ha-Jung (Frontiers in Veterinary Science, 2022)
Case 1, a six-year-old, spayed female Pug, presented with severe systemic urticaria, edema, and erythema. The dog had received a famotidine injection as a treatment for repeated vomiting in another hospital. On physical examination, hyperthermia was observed. Moderate pancytopenia, hypoalbuminemia, and increased CRP and D-dimer were also observed in blood tests. Hyposthenuric proteinuria, pulmonary interstitial infiltration, and hepatomegaly were found in other tests. In the histology of the skin, dermal edema and infiltration of inflammatory cells were observed. Therefore, she was diagnosed with acute systemic hypersensitivity. Case 2, a 13-month-old, neutered male Pembroke welsh corgi, presented with severe and patchy systemic ulcerative skin lesions. The dog had a history of soft feces and pain around the anus 2 days before. Thrombocytopenia, and increased CRP and D-dimer were observed in blood tests. In histology, epidermal necrolysis, separation of the epidermis and dermis, and infiltration of inflammatory cells were observed. Therefore, he was diagnosed with an immune-mediated disease with necrolysis dermatitis. Case 3, a 12-year-old, spayed female Pomeranian, presented with severe systemic alopecia, pustule, and crust on the skin. The dog had received an infection treatment from a local hospital. Severe regenerative anemia (hematocrit 15.3%, negative saline agglutination test, negative slide agglutination test, negative Coomb’s test, prominent spherocytes) elevated liver enzymes, and increased CRP and D-dimer were observed in blood tests. On histopathology of the skin, pustules, acantholytic cells, and inflammatory cells were observed in the keratin layer of the epithelium. Therefore, she was diagnosed with Pemphigus foliaceus concurrent with immune-mediated hemolytic anemia. The 3 cases were diagnosed with fatal immune-mediated skin disease concurrently with hematological and systemic abnormalities. All the cases were treated with immune-suppressive drugs, prednisolone, and cyclosporine. In cases 2 and 3, the dogs also received human intravenous immunoglobulin as an immune modulator. The treatment was successful with significant improvements in all the 3 cases.